2021
DOI: 10.1002/art.41780
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Oral Microbiome in Patients With Early Rheumatoid Arthritis and Individuals at Risk of Rheumatoid Arthritis Compared to Healthy Individuals

Abstract: Objective It has been suggested that rheumatoid arthritis (RA) may originate at the oral mucosa. The aim of the present study was to assess the oral microbiome and periodontal condition in patients with early RA and individuals at risk of developing RA compared to healthy controls. Methods Three groups were recruited (n = 50 participants per group): 1) patients with early RA (meeting the American College of Rheumatology/European Alliance of Associations for Rheumatology 2010 classification criteria), 2) indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…In our study, P. gingivalis was not included among the top 30 most important ASVs for the classification of samples and those with variable importance in projection (VIP) > 1. In agreement with our results, Kroese and colleagues reported that P. gingivalis was not identified as a discriminative zero-radius operational taxonomic units, zOTUs ( Kroese et al., 2021 ). Furthermore, previous 16S rRNA gene sequencing studies, investigating the subgingival microbiome of patients with RA compared to osteoarthritis and healthy controls without periodontitis did not show subgingival compositions discriminating between RA and osteoarthritis ( Mikuls et al., 2018 ), nor between RA and healthy controls regarding the periodontal pathogens P. gingivalis or A. actinomycetemcomitans ( Lopez-Oliva et al., 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, P. gingivalis was not included among the top 30 most important ASVs for the classification of samples and those with variable importance in projection (VIP) > 1. In agreement with our results, Kroese and colleagues reported that P. gingivalis was not identified as a discriminative zero-radius operational taxonomic units, zOTUs ( Kroese et al., 2021 ). Furthermore, previous 16S rRNA gene sequencing studies, investigating the subgingival microbiome of patients with RA compared to osteoarthritis and healthy controls without periodontitis did not show subgingival compositions discriminating between RA and osteoarthritis ( Mikuls et al., 2018 ), nor between RA and healthy controls regarding the periodontal pathogens P. gingivalis or A. actinomycetemcomitans ( Lopez-Oliva et al., 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Since genetic variations in TAS2R38 have functional consequences that, in addition to taste perception, may contribute to antimicrobial responses [18,20], we investigated the buccal microbiome in our RA and non-RA control subjects, many of whom were at risk for developing future RA, and compared the microbiome across TAS2R38 genotypes. Our findings are consistent with other reports finding the enrichment of periodontal pathogens in oral, pulmonary, and gastrointestinal microbiomes obtained from individuals at risk for RA [35][36][37][38][39][40]. Relative depletion of P. gingivalis has been reported in RA patients compared to anti-citrullinated protein autoantibody (ACPA)-positive individuals who are at risk for developing future RA [38].…”
Section: Discussionsupporting
confidence: 92%
“…Cheng et al compared early RA and at risk patients with RA to healthy controls and showed dysbiosis, including an increase of Porphyromonas gingivalis , in the periodontally healthy microbiota (and altered diseased subgingival microbiota) of at risk RA compared with HC [ 35 ]. Kroese et al reported similarities in oral microbiota of early patients with RA and patients with RA at risk, since in both groups, the oral microbiota were characterized by an increased relative abundance of potentially proinflammatory species when compared to that in healthy controls [ 15 ]. Prevotella salivae, Veillonella , and Prevotella were more abundant in the early RA group and RA at risk group compared to the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella salivae, Veillonella , and Prevotella were more abundant in the early RA group and RA at risk group compared to the healthy control group. The genus P gingivalis was not identified in this study as a discriminative microorganism [ 15 ]. The differences in outcomes between the various studies can be explained by differences between study groups, such as including patients at different stages of RA, differences in disease activity, differences in therapy, and including patients at risk or early and established RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation